2023
DOI: 10.3390/molecules28031114
|View full text |Cite
|
Sign up to set email alerts
|

Future Antimicrobials: Natural and Functionalized Phenolics

Abstract: With incidence of antimicrobial resistance rising globally, there is a continuous need for development of new antimicrobial molecules. Phenolic compounds having a versatile scaffold that allows for a broad range of chemical additions; they also exhibit potent antimicrobial activities which can be enhanced significantly through functionalization. Synthetic routes such as esterification, phosphorylation, hydroxylation or enzymatic conjugation may increase the antimicrobial activity of compounds and reduce minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 77 publications
2
71
0
2
Order By: Relevance
“…Previously, it has been mentioned in different studies that DNA might be affected by the probiotic/prebiotic treatments (Aditya et al., 2020; Van Loo et al, 2005). Cell walls of different gram‐negative bacterial pathogens have been observed to be permeable in the presence of CFCS and phenolic compounds leading to the DNA damage (Aditya et al, 2020, Alvarado‐Martinez et al., 2020; Lobiuc et al., 2013). This damaging might be the effect of acidic pH environment created by the phenolic acids and CFCS as well as can be attributed to H 2 O 2 that is present in CFCS (Aditya et al., 2020; Alvarado‐Martinez et al., 2020; Brudzynski et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been mentioned in different studies that DNA might be affected by the probiotic/prebiotic treatments (Aditya et al., 2020; Van Loo et al, 2005). Cell walls of different gram‐negative bacterial pathogens have been observed to be permeable in the presence of CFCS and phenolic compounds leading to the DNA damage (Aditya et al, 2020, Alvarado‐Martinez et al., 2020; Lobiuc et al., 2013). This damaging might be the effect of acidic pH environment created by the phenolic acids and CFCS as well as can be attributed to H 2 O 2 that is present in CFCS (Aditya et al., 2020; Alvarado‐Martinez et al., 2020; Brudzynski et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Natural product extracts, such as geopropolis, tend to exhibit a better antibacterial effect against Gram‐positive bacteria, a fact not observed in our findings for the extract in question. Natural product extracts can exert their antibacterial activity through several mechanisms, including damage to the cell membrane due to the interaction of compounds with essential membrane components, which can lead to its rupture, as well as the inhibition of metabolic processes that hinder the formation of the cell wall and protein synthesis [48,49] …”
Section: Resultsmentioning
confidence: 99%
“…Generally, the phytochemical components in saffron bioproducts can kill or inhibit the growth of bacterial cells in various ways, including (1) disruption of the cell membrane, (2) modulation of efflux pumps, (3) inhibition of virulence factors, (4) inhibition of quorum sensing, (5) inhibition of fatty acid synthase, (6) inhibition of peptidoglycan cross-linking, (7) inhibition of dipeptide synthesis, (8) inhibition of bacterial biofilm formation, (9) alteration in oxidative phosphorylation, and (10) inhibition of oxygen uptake (Figure ). ,, Molecular docking studies of flavonoids showed that flavonoids and their derivatives have significant affinity for binding with certain receptors, suggesting the reason for their good antimicrobial activity …”
Section: Biological Activities Of Saffron Byproductsmentioning
confidence: 99%